Две секунды после: роман / Ладунка К. - Ладунка Ксения (Wattpad. ТОП на русском, 2024)
Экземпляры: аб. ЦБ (20240603) / Инвентарный номер: 21243 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Л 15 / ББК: 84(2Рос=Рус)4-44